The sound of music - Rodgers, Richard 1902-1979; Fink, Bert (A Classic collectible pop-up, 2009)
In a fictionalized account Maria, an Austrian orphan, becomes the governess of the seven children of Captain von Trapp and ends up becoming his wife and mother of the children, as the family makes a daring escape from the Nazis during their singing tour